Effects of Pulsatile Control Algorithms for Diagonal Pump on Hemodynamic Performance and Hemolysis. Issue 1 (29th October 2018) - Wang, Shigang; Force, Madison; Moroi, Morgan K.; Patel, Sunil; Kunselman, Allen R.; Ündar, Akif
Abstract: The objective of this study is to compare hemodynamic performances under different pulsatile control algorithms between Medos DeltaStream DP3 and i‐cor diagonal pumps in simulated pediatric and adult ECLS systems. An additional pilot study was designed to test hemolysis using two pumps during 12h‐ECLS. The experimental circuit consisted of parallel combined pediatric and adult ECLS circuits using an i‐cor pump head and either an i‐cor console or Medos DeltaStream MDC console, a Medos Hilite 2400 LT oxygenator for the pediatric ECLS circuit, and a Medos Hilite 7000 LT oxygenator for the adult ECLS circuit. The circuit was primed with lactated Ringer's solution and human packed red blood cells (hematocrit 40%). Trials were conducted at various flow rates (pediatric circuit: 0.5 and 1L/min; adult circuit: 2 and 4L/min) under nonpulsatile and pulsatile modes (pulsatile amplitude: 1000–5000rpm [1000 rpm increments] for i‐cor pump, 500–2500rpm [500 rpm increments] for Medos pump) at 36°C. In an additional protocol, fresh whole blood was used to test hemolysis under nonpulsatile and pulsatile modes using the two pump systems in adult ECLS circuits. Under pulsatile mode, energy equivalent pressures (EEP) were always greater than mean pressures for the two systems. Total hemodynamic energy (THE) and surplus hemodynamic energy (SHE) levels delivered to the patient increased with increasing pulsatile amplitude and decreased with increasing flow rate. The i‐cor pump outperformed at low flow rates, but the Medos pump performed superiorly at high flow rates. There was no significant difference between two pumps in percentage of THE loss. The plasma free hemoglobin level was always higher in the Medos DP3 pulsatile group at 4 L/min compared to others. Pulsatile control algorithms of Medos and i‐cor consoles had great effects on pulsatility. Although high pulsatile amplitudes delivered higher levels of hemodynamic energy to the patient, the high rotational speeds increased the risk of hemolysis. Use of proper pulsatile amplitude settings and intermittent pulsatile mode are suggested to achieve better pulsatility and decrease the risk of hemolysis. Further optimized pulsatile control algorithms are needed.